HUBUNGAN FREKUENSI MOBILISASI DENGAN PENYEMBUHAN LUKA POST OPERASI BEDAH DIGESTIF - Maria " Ulfa; Wasisto " Utomo; Yesi " Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
ABSTRACT Post surgery, there are several problems that often arise, which are wound trauma during the healing period. Wounds from surgery may cause pain and make patients feel anxious and afraid to do mobilization. This research aimed was to determine the relationship between mobilization frekuensi with wound healing of patient post operation in digestif Dumai Hospitas. This research used descriptive correlation design with cross sectional approach. Sample of this research is 38 samples taken by accidental sampling technique with observing the inclusion criteria. Measuring instrument used in this study were questionnaire and obsevasy sheets. The analysis is for the univariate analysis as well as frequency and percentage of bivariate analysis using Chi-Square test. The results showed that there were no a relationship between mobilization frekuensi with wound healing of patient post degestif  (p value= 0,264 > α 0,05). The results of this study can be a reference for the hospital as well as facilitate the nursing care.  Keyword                : digestive, wound healing, mobilization,